Eye-foot coordination and balance with shooting ability futsal players of SMAN 1 Bungaraya - Sujadesman, Bram (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2025)
Problems: The problem of this in-depth study is the assumption that the shooting accuracy of the players is still not ideal. Purpose: The purpose of this study was to determine whether there is a relationship between lower leg and instep coordination and shooting skills in Futsal at SMAN 1 Bungaraya Siak Regulation. Methods: The review population was 15 students of SMAN 1 Bungaraya Siak Regency whose examination procedure was an all out examination. The test tools used were lower leg coordination tests with the Mitcel Soccer Test and offset tests with standing balance stroke tests, then shooting ability tests. Information investigations were carried out by utilizing the Second Item relationship with SPSS 20. Results: The final results of this study showed: (1) There is a critical relationship between lower leg coordination and shooting ability with the SPSS 20 relationship coefficient esteem t = 0.832 and p esteem = 0.010/2 = 0.005 <0.01. (2) There is a critical relationship between offset and shooting ability with the SPSS 20 esteem coefficient t = 0.963 and p esteem = 0.010/2 = 0.005 < 0.01. (3) There is a very large relationship between lower leg coordination and balance together with the instep shooting ability of futsal players at SMAN 1 Bungaraya Siak Regime with the SPSS 20 esteem coefficient t = 0.961 and p esteem = 0.010/2 = 0.005 < 0.01. Conclusion: physical condition of eye-foot coordination and balance can be used by coaches as a solution and variation to improve abilities. Shooting on goal is based on these findings, taking into account the benefits of physical condition, eye-foot coordination, and balance.